2013
DOI: 10.4143/crt.2013.45.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Aggressiveness of End-of-Life Care for Advanced Stomach Cancer Patients

Abstract: PurposeIt is important to balance the appropriateness of active cancer treatments and end-of-life care to improve the quality of life for terminally ill cancer patients. This study describes the treatment patterns and end-of-life care in terminal gastric cancer patients.Materials and MethodsWe retrospectively analyzed the records of 137 patients with advanced gastric cancer receiving chemotherapy and dying between June 1, 2006 and May 31, 2011. We recorded interval between last chemotherapy dose and death; fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 15 publications
0
33
1
2
Order By: Relevance
“…It also allows for patients and physicians to initiate advance care planning, and to discuss the continuation or discontinuation of life-prolonging treatments. Yet, recent studies have reported trends towards a rising aggressiveness of cancer care in the last months and weeks before death, [28][29][30][31][32] with sizable economic consequences. 33,34 However, very little is known about the use of care and treatments in the last months of life of patients with metastatic melanoma.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…It also allows for patients and physicians to initiate advance care planning, and to discuss the continuation or discontinuation of life-prolonging treatments. Yet, recent studies have reported trends towards a rising aggressiveness of cancer care in the last months and weeks before death, [28][29][30][31][32] with sizable economic consequences. 33,34 However, very little is known about the use of care and treatments in the last months of life of patients with metastatic melanoma.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…It also allows for patients and physicians to initiate advance care planning, and to discuss the continuation or discontinuation of life‐prolonging treatments. Yet, recent studies have reported trends towards a rising aggressiveness of cancer care in the last months and weeks before death, with sizable economic consequences …”
mentioning
confidence: 99%
“…As these guidelines are not always legally binding, physicians are often faced with having to acquiesce to patient's family wishes of refusing to place a patient on DNAR status [23]. It is routine that the primary attending physician discuss DNAR policies with the patients; then, two other physicians who belong to the same department are required to mediate and decide futility [24]. Moreover, the JCI that oversees patient safety and quality of health care internationally requires the signature of the patient or a key member.…”
Section: Evolution Of Dnar Policy In Qatarmentioning
confidence: 99%
“…According to other similar studies, 15% of terminally ill patients receive chemotherapy within their last 2 weeks of life . Some studies have indicated covariations between chemotherapy up to the end of life and unfavorable patient outcomes . When should aggressive therapy be discontinued at the end of life?…”
Section: Introductionmentioning
confidence: 99%